PEMBATASAN HAK ATAS INFORMASI ELEKTRONIK DALAM YURISDIKSI CYBERSPACE - Effendi, Muh (Fakultas Hukum Universitas Gunung Rinjani, 2019)
Writing this thesis aims to find out the form of legal protection and restrictions on the right to information that can be done in cyberspace. Because of the rapid advances in technology, there are also more problems that arise from this virtual world, this is the background of this thesis writing because it is very important to know what can and should not be done according to laws governing the world this virtual. Some countries, including Indonesia, restrict the right to electronic information, although this kind of regulation, both formally and materially, is contrary to the rights of individuals to privacy and information, but there are other people's rights that also need to be protected and state security that must be protected. The birth of law number 11 of 2008 which was revised to law number 19 of 2016 is clear evidence of the limitation of the right to information in Indonesia, because Indonesia upholds human rights but with this law Indonesia also aims to maintain security or country stability. The conclusion reached is: that the state protects the right to information and the use of technology but is also obliged to protect the public interest from all kinds of disturbances arising from misuse of information, especially through electronic media that disturb public order, or so-called jurisdiction.